Just in time, Abraham Lincoln - Polacco, Patricia (G.P. Putnam's Sons, 2011)
When two brothers visit a museum in Harper's Ferry, West Virginia, with their grandmother, they find themselves in a very realistic Civil War setting where they see the Antietam battlefield and meet historical figures from the aftermath of that momentous battle. Includes author's note on the Battle of Antietam.